LEGAL PROTECTION FOR INVESTOR IN CAPITAL MARKET STOCK TRADING - Tito Sofyan (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2013)
ABSTRACTProtection for investor is the crucial issue because it has been foundÂ many evidence of the misuse of companyâ€™s resources for extensive period. Moreover, there are also the case of stock lose, case in IPO, short selling, securities fraud, market manipulation, and insider trading. Stock market is abouttrust, if it lose,Â the market will collpase and it will affect the other sector, mainly economic sector. Undang-UndangNomor 8 Tahun 1995 tentangPasar Modal (UUPM) is one of the legal order to support the development of economy. UUPM have regulatethings that very important in activities in security market, especially the regulation of protection for investor. However, there are still problems that have not been regulated proporsionally, insinkronisasirule of law, and the needs for further explanation for the existing norm. The purpose of this research is to discuss the problem of the needs of investor to get a legal protection, and to discuss the problem of the right of investor in security market that is notÂ provided legal certaintyin Undang- Undang Nomor 8 Tahun 1995 tentangpasar Modal. Furthermore, this researchalso tried to analyze the law conceptionÂ problem that can be developed in the legal protection for the rights of investors in security market in the future so that it can contribute to the development of law in Indonesia. The theory that used to analyze the law material in this research is the contract theory from Grotius, justice theory from John Rawls, legal protection theory from Fitzgerald, Utility theory from Jeremy Bentham, and socialengineering theory from Roscoe Pound. The method that used in this research isnormative law research with rule of law approach, philosophy of law, and law history. The result of the research shows that investor is one of the most important element in security market activities because it fulfill the need of addiltional capital for issuers, develop the market, and one of the stakeholdersbeside the other stakeholders, that is the issuers, management, commissioner,employee, and creditor. But the rights of the investor are oftenly forgotten because of the lack of information towards companyâ€™s resources compared tothat of issuers. Because of that it needs protection from law that fair and balanced, with the norm of law interference that purposefully made by the statebecause the legal protection that is not sufficient with just the norm of freecontract. Regardingthe relationship betweenthe investor and theissuerhasregulated in UUPT, includingtheir rights, butit was not enoughtogivelegal protection toinvestorsin the capital market. Relationship between UUPM and UUPT is Lex Specialis with Lex Generalis. UPM as Lex Specialis and UUPT as Lex Generalis, and as we know that Lex Specialis may differrent from the general provisionsor Lex Generalis. UUPT has authorized the forming of the Act to regulate the rights of investors in UUPM in the future in order to give more legal certainty, especially in the regulated of compensation, full disclosure and criminal provisions. Because of that, the approach of UUPM in security market can be classified in two, that is the institutional approach and activity approach. The Institutonal approach are the existence of Bapepam, stock market, LKP, and LPP. They donâ€™t just having in charge of Perdata but also in charge of public authority that run some of the government function. From activity approach, UUPM consist of limitation for certain party based on the spirit of â€œfair competitionâ€.such as the necessity of transparency, reporting requirements, and restrictions such as market manipulation, insider trading, misleading information, and the regulation of sanctions in administrative, civil, and criminal. The consept that can be developed to increase the protection for investor is to make UUPM give stronger legal framework in the future through the regulation of the protection of investorâ€™s right and maximize the transparency of information for go public company and for company that have not go public yet, as the guarantee of certainty of law that is needed by investor with this step : (1) Make Good Corporate Governance refer to the principle of OECD 2001 as reference for UUPM norm; (2) Demutualisasi stock market to increase the transparency of information and quality of the management as an entity; (3) The development of reporting system and the disclosure of data electronically; (4) Strengthen Bapepam authority as supervisor in supervising the behavior of market player for the organized, fair, and efficient market.Key Words : Protection, Investor, Certainty, Capital Market, Stock Trading